Metodologia participativa para repositórios de recursos educacionais abertos - Grein, Pedro Paulo Boaventura (2016)
This research deals with the use of a participatory design methodology to develop a repository of open educational resources, the Arcaz. Discusses key aspects of neutrality and determinism of technology within the context of Social Studies of Science and Technology and presents some concepts of critical theory of technology related to the democratic construction of technological artifacts. Discusses the philosophical heritage of the movements that led to the emergence of free software, open education and open educational resources and argues that participatory design share similar ideals. It presents concepts of human-computer interaction, interaction design and user centered design, important to enhance the user experience in information systems. It addresses the participatory design as a methodology that allows the democratic participation of users in the technological construction, promoting mutual learning and active voice for the participants. Develops a participatory design methodology adapted to the Arcaz context of use and provides the procedures for the meetings conducted to apply participatory design techniques to the repository and the results obtained. It concludes with a study of some of the interventions suggested in the system and orientations for future applications of participatory practices in the development of the repository and a list of best practices, focusing on ethical principles that should guide the participatory design.